Mechanisms structuring host–parasitoid networks in a global warming context: a review - Thierry, M; Hrček, J; Lewis, O (Wiley, 2019)
1. In natural communities, multiple host and parasitoid species are linked to form complex networks of trophic and non-trophic interactions. Understanding how these networks will respond to global warming is of wide relevance for agriculture and conservation. 2. This study synthesises the emerging evidence surrounding host–parasitoid networks in the context of global warming. The suite of direct and indirect interaction types within host–parasitoid networks is summarised, as well as their sensitivity to temperature changes. The study also compiles and reviews studies investigating the responses of whole host–parasitoid networks to increasing temperatures or proxy variables. The findings reveal there is limited evidence overall for the prediction that parasitism will be reduced under global warming: approximately equal numbers of studies show elevated and reduced parasitism. 3. Increasingly, endosymbiotic bacteria are recognised as influential mediators of host–parasitoid interactions. These endosymbionts can change how individual species respond to global warming, and their effects can cascade to affect whole host–parasitoid networks. The evidence that symbiotic bacteria are likely to affect the response of host–parasitoid networks to global warming is reviewed. Symbionts can protect hosts from their parasitoids or influence thermal tolerance of their host species. Furthermore, the symbionts themselves can be impacted by global warming. 4. Finally, the study considers the most promising avenues for future research into the mechanisms structuring host–parasitoid networks in the context of global warming. Alongside the increasing availability of modern molecular methods to document the structure of real, species-rich host–parasitoid networks, the study highlights the utility of manipulative experiments and mathematical models.